1970
DOI: 10.1037/h0029850
|View full text |Cite
|
Sign up to set email alerts
|

Encoding and decoding of nonverbal affect in humans.

Abstract: Twelve college-age males viewed a sequence of equally spaced and randomly ordered red and green lights, in which the red light signaled the advent of shock. Continuous skin-resistance measures were taken. Subjects' nonverbal responses to the red and green stimuli were video taped without their knowledge and were later viewed by themselves and five of the other subjects, individually, under conditions which required them to discriminate between shock and nonshock trials. The subjects' accuracy scores were above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
2
3

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 15 publications
3
96
2
3
Order By: Relevance
“…First, there is the suggestion and evidence initially proposed by Jones (1935Jones ( , 1950 that expressiveness is negatively related to affective intensity, i.e., the more a person manifests expressive motor changes in emotionally provocative situations, the less he or she will manifest autonomic system changes (equated by Jones as a sign of emotional reactivity). Lanzetta and Kleck (1970) reported data that appeared to support the negative association of expressiveness and feeling when they examined individual differences in expressiveness and autonomic reactivity to threat of shock; subjects whose expressions were indistinct and difficult to judge (presumably less overtly reactive) showed the strongest skin conductance changes.…”
Section: Facial Motor Mechanismmentioning
confidence: 78%
“…First, there is the suggestion and evidence initially proposed by Jones (1935Jones ( , 1950 that expressiveness is negatively related to affective intensity, i.e., the more a person manifests expressive motor changes in emotionally provocative situations, the less he or she will manifest autonomic system changes (equated by Jones as a sign of emotional reactivity). Lanzetta and Kleck (1970) reported data that appeared to support the negative association of expressiveness and feeling when they examined individual differences in expressiveness and autonomic reactivity to threat of shock; subjects whose expressions were indistinct and difficult to judge (presumably less overtly reactive) showed the strongest skin conductance changes.…”
Section: Facial Motor Mechanismmentioning
confidence: 78%
“…For example, regulating one's emotions, due to either stable individual differences in emotional expression or specific instructions to control one's emotions, is arousing (Adelmann & Zajonc, 1989;Gross & Levenson, 1993;Pennebaker, 1985). Inhibiting one's facial expression of emotion or pain also results in increased arousal (Lanzetta & Kleck, 1970;Notarius, Wemple, Ingraham, Bums, & Kollar, 1982). Additionally, research has shown that holding anger in or regulating its expression leads to physiological arousal, such as increased blood pressure, a faster pulse, and decreased skin conductance (Rinkenstein, King, & Drolette, 1954;Haynes, Feinlieb, & Kannel, 1980;Holroyd & Gorkin, 1983;MacDougall, Dembroski, & Krantz, 1981;Schalling, 1985).…”
Section: Strength and Depletionmentioning
confidence: 99%
“…Inter nalizers and externalizers are further charac terized by different patterns of physiological response. In particular, internalizers show higher levels of skin conductance than do externalizers when exposed to emotionally charged stimuli [21,22], Internalizers also show increases in heart rate under these con ditions, whereas externalizers do not [1], A number of studies suggest that the heightened autonomic responses of intemalizers may reflect the work of behavioral inhi bition. Specifically, internalizers work to ac tively suppress emotional expression.…”
Section: Nonverbal Expressiveness and Autonomic Activitymentioning
confidence: 99%